2022
DOI: 10.1002/cam4.4841
|View full text |Cite
|
Sign up to set email alerts
|

Light‐intensity and moderate‐to‐vigorous intensity physical activity among older adult breast cancer survivors with obesity: A narrative review

Abstract: Background With an aging population, rising incidence of breast cancer, improved survival rates, and obesity epidemic, there will be a growing population of older adult breast cancer survivors with obesity. This complex population, often with multimorbidity, is at risk for several poor health outcomes, including recurrence, cardiovascular disease, dementia, and diabetes, and a number of deleterious symptoms, including a worsened inflammatory profile, breast cancer‐ related lymphedema, mobility dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…A study involving 73,435 non-hospitalized patients utilizing the health services of the US Department of Veterans Affairs revealed that all subgroups, including individuals with obesity, are at a higher risk of developing CVD after being infected with COVID-19 [ 3 ]. Furthermore, the group without obesity had a higher hazard ratio than the people with obesity when compared to the contemporary control group in terms of developing CVD after being infected with COVID-19 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study involving 73,435 non-hospitalized patients utilizing the health services of the US Department of Veterans Affairs revealed that all subgroups, including individuals with obesity, are at a higher risk of developing CVD after being infected with COVID-19 [ 3 ]. Furthermore, the group without obesity had a higher hazard ratio than the people with obesity when compared to the contemporary control group in terms of developing CVD after being infected with COVID-19 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2023) conducted a long-term cardiovascular study and found that COVID-19 did not increase the risk of CVD events, including heart failure, stroke, and myocardial infarction, despite adjusting for potential confounding factors such as age, gender, co-morbidities, and medications. However, the study did find a higher risk of CVD events among people who had obesity or diabetes before contracting COVID-19 [ 25 ]. Another study, which used data from the American Heart Association COVID-19 Cardiovascular Disease Registry, indicated that COVID-19 patients with obesity or had a higher BMI were more susceptible to cardiovascular events [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…More consideration may be given to light exercise research in liver cancers with high tumor invasion and symptom burden. Guidelines primarily discuss light exercise to promote activity in people with low fitness 38 40 , based on the assumption that light exercise might act through similar paths as moderate-to-vigorous. Furthermore, Subgroup analysis of exercise trend revealed that maintaining exercise had a more positive impact on CRF than reducing exercise, while reducing exercise was greater than improving exercise.…”
Section: Discussionmentioning
confidence: 99%
“…22,39 While "standard" approaches to fatigue reduction emphasize adherence to a moderate-to-vigorous exercise intervention, it is increasingly understood that lower intensity exercise has been understudied but may be uniquely suited to a fatigued population. 40 Meditative movement practices such as tai chi or qigong may form an ideal version of low-intensity physical exercise that has added benefits for psychological and cognitive health due to the cultivation of meditative awareness. To this end, one recent study directly compared tai chi to standard moderate-tovigorous exercise in older adults with cognitive decline and showed that both groups significantly improved cognitive function, 41 suggesting that such meditative movement practices can improve multiple health outcomes beyond physical function.…”
Section: Introductionmentioning
confidence: 99%